Accomplishments and Challenges Facing Students with Disabilities at the University of Dar es Salaam: Thirty Years of Navigating the Hill - Tungaraza, Frida (Papers in Education and Development, 2018)
The first special schools in Tanzania were established by charitable organizations. Although some children and youth with different special needs are receiving education at present, still the majority of them are not in schools. Some students, who are lucky enough, have attained degrees from different Universities including the University of Dar es Salaam. The University of Dar es Salaam is celebrating thirty years since the first two students with special needs were admitted for degree programs in the academic year 1978/79. Nineteen students with different disabilities were involved in this study. Interviews, documentation and observation methods were used. The results indicate that there are achievements that are worth noting, but tough challenges also persist. One obvious achievement is that the number of students with different special needs, and staff to cater for them has increased. In addition, students are now enrolled in different undergraduate and postgraduate programs. Despite the achievements, students with special needs at the University of Dar es Salaam still have to contend with a plethora of challenges, including accessibility problems and lack of and/or inadequate equipment and materials. The University has the ability to make life easier for persons with disabilities, by making necessary modifications to its environment and making the community aware of these students ' special needs. The celebration of thirty years should be a wake-up call for everyone in the community to work hard and diligently towards meeting the special needs of persons with disabilities.